2017
DOI: 10.1155/2017/6302109
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Nutritional Characterization of Brebas for Fresh Consumption from Nine Fig Varieties (Ficus caricaL.) Grown in Extremadura (Spain)

Abstract: The quality characteristics of brebas for fresh consumption from nine fig varieties at different commercial ripening stages were determined. Physicochemical and nutritional parameters were analyzed for both skin and flesh, and the findings were compared among varieties and ripening stages. The results revealed that the major nutrient components in brebas are sugars, such as glucose and fructose, and mineral elements, including K, Ca, P, and Mg. Most nutrients evaluated are important elements that contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
4
14
1
Order By: Relevance
“…Overall, organic acids, were lower in dark-colored fig cultivars. The findings are in agreements with results reported by Colaric et al (2005) and Pereira et al (2017). According to the same authors, malic and citric acid have been identified as the major organic acids in figs.…”
Section: Organic Acidssupporting
confidence: 91%
“…Overall, organic acids, were lower in dark-colored fig cultivars. The findings are in agreements with results reported by Colaric et al (2005) and Pereira et al (2017). According to the same authors, malic and citric acid have been identified as the major organic acids in figs.…”
Section: Organic Acidssupporting
confidence: 91%
“…Initially, the mean fig firmness values were 2.57 N mm −1 at Stage 1, decreasing to 0.75 N mm −1 at Stage 3. Our results during the ripening process of fig cultivars were similar to those obtained by other authors [17,22]. Regarding cultivar differences, the firmness values of SA and BB were higher than those of most of the cultivars studied, whereas TV presented firmness values significantly lower than the rest of the cultivars for all ripening stages studied.…”
Section: Colour and Firmnesssupporting
confidence: 90%
“…The nine fig tree cultivars studied for fresh consumption in the order of ripening (early, middle or late) were 'San Antonio'(SA), 'Blanca Bétera' (BB), 'Brown Turkey'(BT), 'Tres Voltas L'Any'(TV) as early cultivars, 'Banane'(BN) as mid cultivar, 'Cuello Dama Blanco' (CDB), 'Cuello Dama Negro'(CDN), 'Colar Elche'(CE), and 'De Rey' (DR) as late cultivars. Studies of morphological and molecular characterisation conducted in Spanish germplasm fig indicate that 'Cuello Dama Blanco' and 'Colar Elche' are the same varieties as 'Kadota' and 'Mission', respectively [19][20][21] hand-collected when they were fully mature and were harvested during two consecutive seasons from an experimental orchard established in 2007 and previously described in our previous work [22].…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations